SIMAP (Sistem Informasi Manajemen Arsip) Kantor Desa Sukamandijaya - Suryani, Nining; Fadhil Muhammad Abdurrahman; Evy Priyanti; Girman Sihombing (IMTechno: Journal of Industrial Management and Technology, 2025)
Mail management that uses manual storage often results in errors in data storage and mail search. This web-based archival information system is indispensable. This web-based archive information system aims to change the way letters are stored by reducing the use of paper (paperless). This information system is made using the website. While the programming language uses PHP, Xampp is used to run the web server, MySQL is used for database management. The life flow model used is waterfall, while unit testing uses blackbox testing. With WEB-based mail storage, errors that have occurred so far can be minimized. The purpose of making this website is to create an information system that processes mail archive data so that it is easier to use